DDRE-27. IDH MUTATED GLIOMAS PROMOTE EPILEPTOGENESIS VIA D-2-HYDROXYGLUTARATE DEPENDENT MTOR HYPERACTIVATION. (25th March 2021) - Mortazavi, Armin; Fayed, Islam; Bachani, Muzna; Dowdy, Tyrone; Steiner, Joseph; Maric, Dragan; Yang, Chun Zhang; Larion, Mioara; Ksendzovsky, Alexander; Zaghloul, Kareem
Abstract: INTRODUCTION: Epileptic seizures in patients with low-grade, isocitrate dehydrogenase (IDH) mutated gliomas reach 90%, a major source of morbidity for these patients. Albeit there are multiple features that contribute to tumor related epileptogenesis, IDH mutations are determined to be an independent factor, although the pathogenesis remains poorly understood. We demonstrate IDH-mutated tumors promote epileptogenesis through D-2-hydroxyglutarate (D-2-HG) dependent mTOR hyperactivation and metabolic reprogramming. METHODS: Human epileptic and nonepileptic cortex were identified via subdural electrodes in patients with IDH-mutated gliomas (n=5). An in vitro rat cortical neuronal model on microelectrode arrays were utilized to investigate the role of D-2-HG on neuronal excitability. mTOR and lysine demethylase (KDM) modulators were applied to elucidate the epileptogenic mechanism. Tetrodotoxin was utilized to evaluate the contribution of neuronal activity to mTOR signaling and metabolism. mTOR signaling was evaluated through western blot analysis and multiplex immunofluorescence. Metabolic function were analyzed via Seahorse assays and metabolomic analysis. RESULTS: D-2-HG increased normalized bursting rate in the neuronal cultures (p<0.0001). Inhibition of mTOR with rapamycin corrected bursting levels to control levels. Furthermore, D-2-HG induced mTOR hyperactivation, independent of bursting activity, which correlated with upregulation of mTOR signaling in human epileptic tissue. KDM inhibition resulted in mTOR hyperactivation and neuronal hyperexcitability, which we demonstrated with D-2-HG, succinate, and PFI-90, a small molecule KDM inhibitor. Epileptic cortex and D-2-HG-treated neurons, have distinct metabolisms independent of neuronal activity compared to peritumoral nonepileptic cortex and control, respectively. CONCLUSION: We demonstrate IDH-mutated gliomas promote epileptogenesis through a D-2-HG dependent mTOR hyperactivation via KDM inhibition, a putative mechanism and potential therapeutic targets. Furthermore, we argue mTOR hyperactivation results in metabolic reprogramming, independent of neuronal firing, which may contribute to epileptogenesis, a heretofore unrecognized aspect of pathologic mTOR signaling in neurological diseases.